Rereading Turgenev: Notes In the Margins of His Last Novel - Бержайте, Дагне (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]This article examines the late novels of the Russian writer I. Turgenev and some of the issues regarding the reception of these works. These issues, and our study of them, relate to an established opinion that his last novels – especially the Virgin Soil – demonstrate a clear “decline in realistic mastery.” The author points out that Turgenev has strengthened the ideological tendency of the last novel after he had received suggestions and comments by some of his contemporaries, mostly by the literary critic P. Annenkov. For this reason, the objective and lyrical manner of Turgenev’s style that was previously so typical of his earlier writings had almost disappeared. However, new elements emerged in the last novel, among which it is possible to notice rather clear allusions to the works of other Russian writers. It is possible to distinguish at least three allusive addresses that are links to M. Mikhailov’s novel Together, F. Dostoyevsky’s The Possessed and N. Gogol’s story Old-World Landlords. In this article, it is concluded that the story by Gogol, which examines the mystery of death, can be understood as a particular code of the Virgin Soil and can aid in reading the work as a philosophical novel about eternal love and the inevitable end of life. Such a philosophical background erases all the ideological searches and disagreements of the contemporaries typical of any particular period in Russia’s history.Grįžtant prie Turgenevo: pastabos paskutinio romano paraštėseStraipsnyje nagrinėjami vėlyvieji rusų rašytojo Ivano Turgenevo romanai ir kai kurie jų recepcijos klausimai, susiję su dar rašytojo laikais įsitvirtinusia nuostata apie tai, jog juose, ypatingai Naujajame bare, jaučiamas akivaizdus „realistinio meistriškumo smukimas“. Straipsnio autorė atkreipia dėmesį, kad rašytojas, atsižvelgdamas į savo amžininkų, labiausiai kritiko P. Annenkovo, pastabas ir pasiūlymus, sustiprino ideologinį paskutinio romano tendencingumą. Dėl šios priežasties jame nebeliko ankstesniems tekstams būdingos objektyvios rašymo manieros bei lyriškumo. Tačiau kartu romane Naujasis baras atsirado nauji elementai, tarp kurių pastebimos gana aiškios kitų rusų rašytojų kūrybos aliuzijos. Straipsnio autorės nuomone Naujajame bare galima išskirti tris aliuzijų adresus: M. Michailovo romaną Kartu, F. Dostojevskio Demonus ir N. Gogolio apysaką „Senųjų laikų dvarininkai“. Straipsnyje daroma išvada, kad pastarasis tekstas, pasakojantis apie mirtį, tampa savotišku ir paslėptu romano kodu. Jį pasitelkus, „Naująjį barą“ galima perskaityti kaip filosofinį romaną apie amžiną meilę ir neišvengiamą gyvenimo pabaigą, kuri nustelbia visus jo amžininkų ieškojimus ir ideologinius nesutarimus, būdingus kiekvienam konkrečiam Rusijos istorijos periodui.
Keywords: Turgenev, “Fathers and Sons“, “Smoke”, “Virgin Soil”, Dostoevsky, “The Possessed”, Gogol, “Old-world Landlords“